Geometric Foliations of Hilbert Manifolds and the Emergence of Spacetime - Polin, Sujana Azmi (Feni University Journal, 2026)
The Author introduces a novel geometric framework in which the observable universe is realized as a three-dimensional slice embedded within an infinite-dimensional Hilbert manifold. Unlike conventional approaches, which treat the universe as a selfcontained manifold, our construction provides a rigorous embedding of compact Riemannian 3-manifolds into separable Hilbert spaces, yielding. Smooth foliations generated by unit-length normal vector fields. This yields a moduli space of embedded universes, modeled as a smooth, infinite-dimensional Fréchet manifold —a structure not previously explored in this context. Extending the framework into a quantum fieldtheoretic setting, The Author defines global fields over the ambient Hilbert space and interpret physical observables as restrictions to individual slices. This gives rise to a fiber bundle of Hilbert spaces indexed by foliation parameters, supporting a relational interpretation in which field configurations, locality, and even dimensionality emerge from the geometry of slicing. As a concrete example, The Author embeds the 3-sphere into l2 and visualize the resulting foliation. The Author concludes by discussing the implications of this approach for the emergence of physical law, the ontological status of the ambient space, and the geometric origin of dimensionality. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (133-150)